Association Between Systemic Immune-Inflammation Index in Early Pregnancy and Preeclampsia: A Multicenter Cohort Study - Li Q; Li M; Zhao C; Chen X; Zhang C; Li Y; Chen Y; Yue C (Journal of Inflammation Research, 2025)
Qiong Li,1,* Meng Li,2,* Chenyang Zhao,1 Xiaohu Chen,3 Chunyi Zhang,3 Ying Li,4 Yu Chen,4 Chaoyan Yue3 1Department of Obstetrics and Gynecology, The First People’s Hospital of Chenzhou, Chenzhou, People’s Republic of China; 2Department of Ultrasound, Obstetrics & Gynecology Hospital of Fudan University, Shanghai Key Lab of Reproduction and Development, Shanghai Key Lab of Female Reproductive Endocrine Related Diseases, Shanghai, People’s Republic of China; 3Department of Laboratory Medicine, Obstetrics & Gynecology Hospital of Fudan University, Shanghai Key Lab of Reproduction and Development, Shanghai Key Lab of Female Reproductive Endocrine Related Diseases, Shanghai, People’s Republic of China; 4Department of Obstetrics, Women’s Hospital of Jiangnan University, Wuxi Maternity and Child Health Care Hospital, Wuxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Chen, Department of Obstetrics, Women’s Hospital of Jiangnan University, Wuxi Maternity and Child Health Care Hospital, Huaishu Alley, No. 48, Liangxi District, Wuxi, 214001, People’s Republic of China, Email tt-seven@126.com Chaoyan Yue, Department of Laboratory Medicine, Obstetrics and Gynecology Hospital of Fudan University, Shanghai Key Lab of Reproduction and Development, Shanghai Key Lab of Female Reproductive Endocrine Related Diseases, Fang Xie Road, No. 419, Shanghai, 200000, People’s Republic of China, Email 20111250007@fudan.edu.cnObjective: The systemic immune-inflammation index (SII) is an effective indicator for evaluating systemic immune-inflammatory responses. The development of preeclampsia (PE) may be attributed to an excessive systemic inflammatory response in pregnant women, however, the relationship between SII and PE remains unclear.Methods: This study included 47,480 singleton pregnant women from three hospitals, comprising 2489 PE patients and 34,835 healthy controls. The gestational age for SII detection is 11.59 ± 3.98 weeks. Participants were divided into four groups based on the quartiles of SII calculated at baseline. Multivariable logistic regression and smooth fitting curves were used to analyze the relationship between SII and PE. Subgroup analyses based on age, BMI, and parity were conducted, and interaction tests were performed to assess the impact of different subgroups on the outcomes.Results: After adjusting for relevant confounding factors, we observed that compared to SII Q1, participants in SII Q4 had a 21% increased risk of PE (OR = 1.21, 95% CI: 1.05– 1.39, P = 0.0078) and a 12% increased risk of preterm birth (OR = 1.12, 95% CI: 1.00– 1.26, P = 0.0488). Smooth fitting curves indicate that the risk of PE increases as SII rises. In subgroups of women aged ≥ 35 years and those with a BMI > 24, SII Q4 was significantly associated with an increased risk of PE compared to SII Q1. Interaction tests showed that BMI and parity did not significantly influence this positive correlation (interaction P > 0.05). Age may affect the association between SII and PE (interaction P < 0.05), with a more pronounced positive correlation observed in women aged ≥ 35 years.Conclusion: The results indicate that elevated SII in early pregnancy is a potential marker associated with an increased risk of PE.Keywords: systemic immune-inflammation index, preeclampsia, multicenter cohort study